Witnessing floral evolution: a case study from Barakar formation in Lajkura colliery, Ib-river coalfield, Mahanadi Basin, India. (2nd January 2022) - Goswami, Shreerup; Singh, Kamal Jeet; Saxena, Anju; Wang, Jun; Chandra, Shaila; Gupta, Suyash
ABSTRACT: Signatures for evolutionary trends have been observed in various glossopterid elements ora recovered from a single stratigraphic succession of Barakar Formation (Artinskian-Kungurian) of Lajkura Colliery, Ib River Coalfield. Significant variations in morphographic characters pertaining mainly to the non-existence/existence of midrib and venation pattern occurring in various species from older to younger horizons reveal two distinct assemblage zones. Assemblage zone–I (oldest, I st horizon) consists of leaf genera- Noeggerathiopsis, Cordaites, Euryphyllum, Kawizophyllum, Buriadia, Gangamopteris, and Glossopteris whereas Assemblage zone-II (2 nd, 3 rd and 4 th horizons) consists of leaf genera Palaeovittaria, Raniganjia, Bengalia, Ginkgoites and Glossopteris . Barring few overlapping Glossopteris species all four horizons have their distinct sets of Glossopteris species. A gradual shift of Glossopteris species with narrow-mesh forms having evanescent and thin midribs in the I st horizon to broad and middle-mesh forms with thick midribs in the youngest 4 th horizon, through middle-mesh forms with moderately thick midribs in 2 nd and 3 rd horizons has been noticed. The occurrence of distinct sets of taxa in successive coal seams demonstrates a characteristic pattern of floral distribution suggesting evolution in glossopterids, and prevalence of some specific climatic conditions during the deposition of these coal seams influencing origin and development of such distinct set of species.